Digital students go to campus: did stress and anxiety affect the intention for organization? - Panduwiyasa, Haryasena; Wibowo, Ferdian Surya (Journal of Education and Learning (EduLearn), 2024)
The study delves into the behavioral shifts observed in "digital students" transitioning from distance to onsite learning during the Generation Z era, influenced significantly by the disruptive effects of the COVID-19 pandemic. Technological advancements have reshaped students' perspectives, rendering educational and organizational engagements more accessible via platforms like video conferencing. However, the return to onsite learning has prompted a notable culture shock, leading to heightened levels of stress and anxiety among digital students. This research aims to examine the psychological ramifications of stress and anxiety on post-pandemic student attitudes toward extracurricular organizational intention. Employing the depression anxiety stress scale (DASS-42) and conducting multiple linear regression analysis on a sample of 420 respondents, the study reveals a significant negative impact of stress level (-35.6%) on students' intentions to engage in organizational activities. Additionally, anxiety levels contribute to a variation of -6.8%. These findings underscore the intricate relationship between psychological factors and student participation, underscoring the imperative to address stress and anxiety to foster robust involvement in campus organizational endeavors.